Perawatan Maloklusi Kelas 1 Angle dengan Agenese Gigi 12, 14, 34, 44 dan Gangguan Sendi Temporomandibular dengan Alat Ortodontik Cekat Teknik Begg Disertai Pemakaian Trainer For Braces - Komang Sri Mahayeni; Prihandini Iman (Faculty of Dentistry, Universitas Gadjah Mada, 2012)
Background: TMJ disorder is define as a condition of acute or chronic inflammation of TMJ in association with mandibular, myofunctional condition, teeth malposition and or malocclusion. TMJ disorder could lead to significant pain and anatomical damage. There are signs and symptoms of TMJ disorder, such as devition of jaw movement, clicking when openingor close the jaw, mastication disorder and decreasing interincisal distance. Purpose: To describe the result of orthodontic treatment with begg technique and trainer for braces on angle’s class I malocclusion with agenese involving 12, 14, 34, and 44 along with TMJ disorder and bad habit which is one side mastication. Case: 19 years old female complaining limited mouth opening, pain on the right side of TMJ when opening the mouth and when chewing hard food and also complaining of multiple diastema on upper and lower teeth. Diagnose : Angle’s class I with bidental protrusive, 3mm midline midline shifting to the left side, agenese involving 12,13,34,44, and one side mastication. Treatment : Patient treated witg begg technique and braces which is wear 1 hour at day time distance, and feel comfort when chewing hard foord and after 24 months of treatment with fixed begg appliance, malposition and interdigitation are corrected.